Pendidikan Berbasis Karakter: Solusi Untuk Meningkatkan Perilaku Sopan dan Santun Siswa - Budi Juliardi; Yuherman Yuherman; Tiara Wulandari (Bakaba : Jurnal Sejarah, Kebudayaan dan Kependidikan, 2018)
Courteous and friendly attitude is a characteristic of the Indonesian people long ago. However, this attitude has begun to erode by the times. Adolescents in particular no longer have a polite attitude, both to parents especially to others. Therefore, polite attitude must be developed again. Educational institutions have a central role in the process of developing polite attitudes through character-based education processes.